Determinants of information communication and smart home automation technology adoption for aging-in-place. Issue 2 (1st May 2020) - Arthanat, Sajay; Chang, Hong; Wilcox, John
Abstract : Purpose: Smart home (SH) internet of things can promote home safety, health monitoring and independence of older adults to age-in-place. Despite its commercial growth, low adoption rates of the technology among aging consumers remain a major barrier. The purpose of this study is to examine SH technology ownership of older adults and its causal pathways with demographics, health and functioning, home safety and information communication technology (ICT) use. Design/methodology/approach: A survey on technology-mediated aging-in-place was completed by 447 respondents, 65 years and older. Structural equation modeling was used to underscore the causal pathways among demographics, health, independence and home safety, ICT and home automation technology adoption. Findings: The study found that ICT usability, home security and independence have a significant direct effect on SH ownership. Demographics had no significant direct effect, but its influence was mediated through ICT usability. With home safety as mediator, physical impairment, falls and accidents and independence had a significant association with SH ownership. Similarly, increased social support (mediated through home security) decreased the probability of SH automation ownership. Originality/value: The findings signify the perceived usefulness of SH automation as theorized in technology acceptance models.